Effect of Bali cattle ovarian status on oocytes nuclear maturation and in vitro fertilization rate - Herry Sonjaya; M. Yusuf; A. Hamdana; Renny Fatmyah Utamy; Sri Gustina; Hasbi Hasbi (Jurnal Ilmu Ternak dan Veteriner, 2017)
The aim of this study was to investigate whether the reproductive status influences the nuclear maturation and fertilization rates of bali cattle oocytes in vitro. Several pairs of ovary were classified into four groups: 1) ovaries with Corpus Luteum (CL) and Dominant Follicle (DF), 2) ovaries without CL and with DF, 3) ovaries with CL and without DF, 4) ovaries without both CL and DF. In the first experiment, oocytes were collected by slicing method in Phosphate Buffer Saline (PBS) medium supplemented with 10% Fetal Bovine Serum (FBS) and 100 IU/ml penicillin streptomycin. Oocytes were matured in tissue culture medium (TCM)-199 supplemented with 10% Fetal Bovine Serum (FBS), 10 IU/ml Follicle Stimulating Hormone (FSH), 10 IU/ml Luteinizing Hormone (LH), and 50 μg/ml gentamycin. Oocytes were matured in 5% CO2 incubator, 38oC for 24 h. In the second experiment, oocytes were matured and then fertilized in vitro to observe pronuclear formation. The first experiment showed that the percentage of oocytes reached methaphase-II (MII) stage on ovaries with CL and without DF (89.47%) were higher (P<0,01) compared to ovaries without both CL and DF (75,47%), ovaries without CL and with DF (74.,41%), or ovaries with CL and DF (65,52%). The result of second experiment showed that the ovarian reproductive status was not significantly different (P>0.05) on fertilization rate.